OPENNESS TO EXPERIENCE AND ONLINE SHOPPING INTENTION: A META-ANALYSIS - Wahyu Rahardjo; Mardianti Mardianti (Universitas Gunadarma, 2023)
Previous published research has shown a correlation between openness to experience and online shopping intention. However, there is no research that reveals how true r and size effect are from the correlation of the two variables. This meta-analysis aims to measure the correlation between openness to experience and online shopping intention by considering the effect size. The total sample of this research is 14747 people from 17 studies who are considered eligible. The findings of this meta-analysis show that openness to experience has a significant positive correlation with online shopping intention at a weak level with 95% CI (0.09; 0.33). Similar results were also found in the group of internet users (95% CI [0.10; 0.36]), and the group of college students (95% CI [-0.240; 0.320]). The heterogeneity test showed good results and there was no publication bias.